The teaching knowledge of the pedagogical coordinators: threads and beads of a beautiful necklace - Souza, Caroline Vieira de (2022)
The article presents a study on the teaching knowledge of five Pedagogical Coordinators from the municipal public school in Ribeirão Preto - SP. We assume that, just like teachers exercising their role, coordinators mobilize, build and reconstruct teacher knowledge in the actions they perform. The study was developed through semi-structured interviews, in a qualitative approach. The results reveal that being an articulator, facilitator and teachers' development professional, the coordinators explicitly verbalize teaching knowledge about their role. In addition, when reporting their practices, they adopt actions that promote dialogue and build partnerships in schools, identifying obstacles that might impair their role as teachers educators. From the practices described, we infer that the actions reported by the coordinators reveal professional knowledge of teaching not verbalized at first by these professionals, but could be observed in their practice.